Polskie jednostki policyjne do walki z terroryzmem - Tomaszewski, Patryk (Historia i Polityka, 2012)
This article seeks to present the scope and forms of activity of the police in the fight against terrorism. The police is the service, which due to the importance of building and maintaining security and public order, often is the first to respond to the terrorist threats. The article discusses the structure of the police anti-terrorist system with particular consideration of the characteristics of diff erent police formations.